Cross-border acquisitions and firm internationalisation : the case of Sogrape and Cotesi - Rodrigues, Carolina Marques Leite Alves (2020)
In a globalised world like today, new challenges are imposed on national companies and products. Internationalisation emerges as an imperative for the survival of organizations. There is rich literature in the field of the cross-border acquisitions. However, it is focused on its pre- and post-acquisition process, taking a financial, accounting and human resource’s perspectives. There is a gap in the study of cross-border acquisitions in an international business perspective. Therefore, this multiple case study research will analyse the effect of cross-border acquisitions in the firm internationalisation of two Portuguese multinational firms, which have several years of existence. In this way, the aim of this study is to realise how did these companies grew in the international arena through cycles of cross-border acquisitions, their organisational background, strategies adopted to the expansion of the brand and product to foreign markets and what was the role of the business networks. In the end, it is possible to understand the effect of cross-border acquisitions in their internationalisation process and how did they strengthened their positions within their business networks, becoming world leading companies.